Pengaruh Penerapan Model Pembelajaran Discovery Learning Berbantuan Media Edukasi Video Tiktok Terhadap Hasil Belajar Siswa Kelas XII MIPA SMAN 10 Luwu - Yunus, Nur Muhajirah; Riskayanti; Al Anshori, Fitrah (Universitas Cokroaminoto Palopo, 2024)
This study aims to determine the effect of implementing the Discovery Learning learning model assisted by Tiktok video educational media on the learning outcomes of class XII MIPA students of SMAN 10 Luwu on the material of Growth and Development of Living Things. The type of research used is a quasi-experiment with a non-equivalent control group design. The instrument used in the study was a learning outcome test. Sampling was carried out using a purposive sampling technique. The sample in this study was class XII MIPA 6 as the experimental class and class XII MIPA 5 as the control class. The data analysis technique used was descriptive and inferential statistical analysis. The results of this study indicate that: (1) the learning outcomes of students taught using the Discovery Learning learning model assisted by Tiktok video educational media obtained an average pretest value of 36.03 with a very poor category and the posttest learning outcomes obtained an average value of 88.73 with a high category; (2) the results of the hypothesis test obtained a sig value of 0.000 <0.05, which means that H0 is rejected and H1 is accepted. Based on this explanation, it can be concluded that there is a significant influence of the application of the Discovery Learning learning model assisted by Tiktok video educational media on the learning outcomes of class XII MIPA students at SMAN 10 Luwu.